ANALISIS SWOT DENGAN IFE & EFE DAN BUSINESS MODEL CANVAS PADA BUDIDAYA BURUNG KICAU DI KABUPATEN BANDUNG - Mochammad Zulfiqar; Rama Candra Jaya; Wildan Guretno Prasetiyo; Ahmad Taufiq Maulana Ramdan (Komunitas Manajemen Kompetitif, 2026)
Bird keeping and breeding is a livestock business that holds significant economic, social, and cultural value for communities, particularly in Bandung Regency. This study aims to (1) identify and analyze internal factors (strengths and weaknesses) in the songbird breeding business in Bandung Regency, (2) identify and analyze external factors (opportunities and threats) in the songbird breeding business in Bandung Regency, (3) map the business model (Business Model Canvas) of the songbird breeding business in Bandung Regency, and (4) formulate development strategies for the songbird breeding business in Bandung Regency based on SWOT analysis (IFE & EFE) and Business Model Canvas. This research employs a descriptive qualitative approach with a case study method. The research was conducted in Bandung Regency, West Java Province, with 5 informants who were songbird breeders selected through purposive sampling. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis utilized SWOT analysis complemented by IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) matrices, as well as the Business Model Canvas (BMC). The results showed that the total IFE score was 2.91 and the total EFE score was 2.81, indicating that the internal and external positions of the business are in the moderate category. Based on the SWOT diagram coordinates, the coordinate point was (1.47 ; 1.17), placing the business in Quadrant I (Aggressive/Growth Oriented Strategy). The main strength factor was superior bloodline breeding stock (0.60), while the main weakness was the absence of financial record-keeping (0.20). The main opportunity factor was the trend of bird-keeping hobbies (0.60), while the main threat was business competition (0.28). The Business Model Canvas mapping revealed that the business already has nine integrated BMC elements, yet improvements are still needed in digital technology utilization for marketing and operational cost efficiency. Recommended strategies include participating in bird contests, utilizing online platforms, joining bird enthusiast communities, developing financial record-keeping, creating social media accounts, seeking alternative feed suppliers, and establishing price standards. The conclusion of this study is that the songbird breeding business in Bandung Regency has good potential for development through aggressive strategies that leverage internal strengths to capture available external opportunities